Stalin’s humanitarian government: class, child homelessness and state security in a historical perspective (1930s–40s) - Franco, Rosaria (Taylor & Francis, 2017)
Informed by Didier Fassin’s concept of humanitarian government, this article reveals a distinct pattern of secret care provisions imposed under Stalin by the secret police and its successor agencies (NKVD, MVD) first to the peasant children displaced by class war and the famine of 1932–33, and then to the children made homeless by the Great Terror and the 1940s’ national deportations. The article also identifies the under-researched reception centres as crucial sites for both administering emergency assistance and establishing the social classification necessary to apply these discriminatory measures. Affected by the decreasing faith in their possible socialist rehabilitation and lack of any official display of compassion, these children’s lives appeared even less worthy of saving in the course of major emergencies. These findings challenge the official Soviet view of the existence of a universal childhood worth protecting, which guided the first socialist country’s intervention to save other children nationally and internationally.